Modalities and essentials of simulation facility for facilitation of clinical skills to medical and nursing students: Need for the present era - Rakesh Sharma; A S Vishwas; Prasuna Jelly; Lisa Chadha; Shine Stephen; Shalinee Rao (Wolters Kluwer Medknow Publications, 2022)
The use of simulation is a unique teaching-learning approach in medical and nursing education to empower undergraduates with desired clinical skills. Simulation duplicates the events from the real world and influences the learner in a naturalistic setup and evokes a real experience to the learner. This method of learning facilitates students to practice multiple times to attain proficiency in a particular technique without compromising on patient safety. They can rely on simulation exercises in clinical skill laboratories (CSL), which boost their confidence level, reduce anxiety, and promote satisfaction before performing or dealing in real clinical settings. Simulation has been widely used for formative evaluation and is a reliable assessment tool as it ensures a high level of objectivity. The simulation-based approach in undergraduate medical and nursing education is an effective way of learning that can be incorporated into the educational strategy. This article presents the evolutionary growth, modalities, prerequisites, usefulness, and challenges for simulation-based learning.